Knowledge of Religion and Religiosity of Santri and Their Influence on the Pluralism - Latifah Nuraini; Ahmad Nashiruddin (The Institute of Research and Service Community IPMAFA Pati, 2021)
This study aims to determine how the influence of religious knowledge and religiosity on pluralism of students Kajen. This research is quantitative with three variables, they are religious knowledge and religiosity as independent variables, and pluralism as dependent variable. Data analyzing of this research used the correlation of product moment for the partial test, and linear regression test for the simultaneous test. The results of data analysis to the 136 samples showed that there is a positive and significant correlation between religious knowledge and pluralism, it shown by the value of sig is smaller than the value of alpha. Furthermore, the second hypothesis test showed the same results that there is a positive and significant relationship between religiosity and pluralism, the value of sig 0,000<α (0,05). Simultaneous test of the relationship between religious knowledge and religiosity on pluralism indicated the value of Fcalculate 13,474 >3,00, it means that religious knowledge and religiosity influence together on pluralism. Equation of regression’s line Y=0,511X_1+0,274X_2+44,728, showed that the value of coefficient X1 and X2 is positive, means both of them influence on pluralism positively (Y).